Level of Occupational Safety and Health among the workers who have been exposed to work injuries in the industrial companies, in the Light of Some Variables - محمد, سهيلة (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Level of Occupational Safety and Health among the workers who have been exposed to work injuries in the industrial companies, in the Light of Some Variables Field study in the General Organization for Social Insurance Lattakia Governorate Sohaila Mohammad Dr. Abstract The objective of this study is to know the level of Occupational Safety and Health among the workers who have been exposed to work injuries in the industrial companies at Latakia Governorate, and identify the differences in the level of Occupational Safety and Health by (age, type of employment, and years of service variable). -The sample of the study consisted of (470) workers who have been exposed to work injuries. . A questionnaire were conducted to option data, which consists of (27) items, after it was judged and modified to fit the current study Many statistical significant were used such as descriptive methods, Arithmetic average, percentages, repetitions, Scheffe Test, and One-way-ANOVA were used in this study - The study showed the following results: - The level of Occupational Safety and Health for the workers who have been exposed to work injuries in the industrial companies at Latakia Governorate was (46,38%) law, ( 35,53%) medium and (18,9%) high - And the results show statistical significant differences in Occupational Safety and Health among the sample members according to the variables, (age, type of employment, and years of service) At significant level of (0,05), (0,01). Based on the study outcomes, the researcher presents some suggestions, the most important is to insure on the role of managements in response to implement the occupational safety and health procedures.